Factors associated with dietary diversity and physical activity of pregnant women in Bangladesh: A cross‐sectional study at an antenatal care setting - Satyajit Kundu; Dilruba Easmin Jharna; Md. Hasan Al Banna; Md Shafiqul Islam Khan (Wiley, 2021)
Abstract Introduction Both dietary diversity and physical activity during pregnancy are very important since they are known to affect pregnancy and birth outcomes. However, little is documented on dietary diversity and physical activity among pregnant women in Bangladesh. Accordingly, this study was designed to assess the dietary diversity and physical activity level, as well as their associated factors, among pregnant women at an antenatal care setting in Bangladesh. Methods An institution‐based cross‐sectional study was conducted with 96 randomly selected pregnant women who sought antenatal care at a hospital in Khulna City, Bangladesh in July 2020. Dietary diversity and physical activity were assessed using the 24‐h dietary recall method of consuming seven food groups, and standardized Pregnancy Physical Activity Questionnaire (PPAQ), respectively. Simple and multivariable logistic regressions were conducted to determine the factors associated with dietary diversity and physical activity among pregnant women. Results Around 70% of participants had high dietary diversity and 58.3% were physically active. Being job holders, getting counseling on diet, and being from higher income and food‐secured families were identified as potential determinants of the high dietary diversity of participants. Having higher secondary education, being job holders, and being from families with a size of below five were more likely to be physically active compared to others. Conclusion In light of these findings, there is a need to support existing policies and devise new policies targeting these variables. Improving awareness on the importance of dietary diversity during pregnancy, incorporating counseling services, ensuring household food security especially during this pandemic situation, and providing women with diet counseling are recommended to increase pregnant women's dietary diversity and physical activity level.